The needs for developing LKPD based on differentiation learning to increase interest and learning results - Maskhanah, Ifa; Medina, Pinta (Research in Education and Technology (REGY), 2024)
Media development in learning needs to be done to achieve learning objectives. This research aims to analyze the need for developing LKPD media based on differentiated learning to increase interest and learning outcomes in Biology. The need to develop LKPD based on differentiated learning is an effort to overcome the problem of interest and learning outcomes in Biology which are still low among Phase E students. SMA Negeri 19 Tebo. The research method was carried out quantitatively from the results of filling in the instrument through several stages, namely observation, articles review, preparation of instruments, filling in the instrument, and data tabulation. The subjects of this needs analysis were all 27 Phase E students of SMA Negeri 19 Tebo. The result of this need analysis showed that the development of LKPD based on differentiated learning was needed to increase the interest and learning outcomes in Biology for SMA Negeri 19 Tebo students. The limitation of this LKPD development needs analysis was the limited number of research samples.